Penerapan terapi okupasi ecoprint terhadap penurunan frekuensi halusinasi pendengaran - Mahendra, Mesha; Oktaviana, Wita; Sriyanto, Heru (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Schizophrenia is one of the cases often found in Indonesia, one of the symptoms is hallucinations. Hallucinations are sensory perception disorders experienced by sufferers such as feeling unreal sensations. One therapy that can be done on individuals who experience hallucinations is occupational therapy with ecoprint batik media. Purpose: To determine the impact of the application of ecoprint therapy on reducing the frequency of auditory hallucinations. Method: A pre-experimental design with a before-after study approach. This study involved 6 respondents who met the inclusion criteria, namely patients who were hospitalized for at least 3 days in the sub-acute room, experienced auditory hallucinations and were cooperative. The intervention given was in the form of eco-print batik-making activities. Results: Based on demographic data, it is known that the patients are aged between 28-67 years and all are male. All patients are Muslim and most of them have elementary and high school education. From the total sample, 3 patients are married and 3 patients are single. The patients' occupations vary, including farmers, laborers, students, and some are unemployed. Paired sample test analysis obtained an average frequency of pre-test hallucinations of 33.33, while in the post-test 24.00, the average difference is 9.3 and the confidence level ranges from 7,496-11,171. The p-value obtained shows a significance value of 0.00 (<0.05). Conclusion: Ecoprint therapy is effective in reducing the signs and symptoms of hallucinations in patients with auditory hallucinations. Keywords: Auditory Hallucinations; Cognitive; Ecoprint; Occupational Therapy; Schizophrenia. Pendahuluan: Skizofrenia merupakan kasus yang banyak ditemukan di Indonesia, salah satu gejalanya yaitu halusinasi. Halusinasi adalah gangguan persepsi sensori, dimana penderitanya merasakan sensasi yang tidak nyata. Salah satu terapi yang dapat dilakukan pada individu yang mengalami halusinasi adalah terapi okupasi dengan media batik ecoprint. Tujuan: Untuk mengetahui dampak dari penerapan terapi ecoprint terhadap penurunan frekuensi halusinasi pendengaran. Metode: Desain pre-eksperimental dengan pendekatan before-after study. Penelitian ini melibatkan 6 responden yang memenuhi kriteria inklusi, yaitu pasien yang dirawat inap minimal 3 hari di ruang subacute, mengalami halusinasi pendengaran, dan bersikap kooperatif. Intervensi yang diberikan berupa kegiatan membuat batik ecoprint. Hasil: Berdasarkan data demografi, diketahui bahwa pasien berusia antara 28-67 tahun dan seluruhnya adalah laki-laki. Semua pasien memeluk agama Islam dan sebagian besar memiliki pendidikan terakhir di tingkat SD dan SMA. Dari total sampel, 3 pasien berstatus menikah dan 3 pasien lajang. Pekerjaannya bervariasi, termasuk sebagai petani, buruh, pelajar, dan ada yang tidak bekerja. Analisis paired sample test didapatkan rata-rata frekuensi halusinasi pre-test adalah 33.33, sedangkan pada post-test 24.00, selisih rata-rata sebesar 9.3 dan tingkat kepercayaan berkisar antara 7.496-11.171. Perolehan p-value menunjukkan nilai signifikansi sebesar 0.00 (<0.05). Simpulan: Terapi ecoprint efektif dalam mengurangi tanda dan gejala halusinasi pada pasien halusinasi pendengaran. Kata Kunci: Ecoprint; Halusinasi Pendengaran; Skizofrenia; Terapi Okupasi.